Performa Reproduksi Induk Bandeng (Chanos chanos) yang Diberi Pakan Kaya Bubuk Spirulina - Lisa Ruliaty; Abidin Nur; I. R. Amalia; A. L. Nurhayati (Prosiding Simposium Nasional Kelautan dan Perikanan, 2022)
The enrichment of broodstock milkfish feed with Spirulina flour has been carried out at the Milkfish Hatchery Unit, MCBA Jepara. This research aims to improve the reproductive performance and quality of the milkfish's eggs. For every 10 kg of pellet feed is enriched with a mixture of 10 pieces of duck eggs, 100 mL of honey, 6 g of vitamin C, 3 g of vitamin E and Spirulina flour dosage of 0.6 g / kg and 1.8 g / kg. These materials are mixed and blended into an emulsion. The emulsion is sprayed evenly onto the pellet’s surface and left to dry.. The amount of pellet feed for broodstock milkfish is 2-3% biomass / day both in the morning and evening. The result shows that the enrichment of broodstock milkfish feed with Spirulina flour affected on : (a) enhancement in the number of eggs (from normally 6.9 million eggs becomes 20 million eggs), (b) frequency of lay eggs (from normally 10 times/month becomes 18 times/month), (c). fertilization degree (from normally 48.5 % becomes 70.4 %), and (d) hatching degree (from normally 66.2 % becomes 79.2 %). However, the enhancement dosage of Spirulina up to three times (from 0.6 g/kg become 1.8 g/kg) does not give significant results.